Vulnerabilities and fisheries impacts: the uncertain future of manta and devil rays. Issue 3 (3rd November 2015) - Croll, Donald A.; Dewar, Heidi; Dulvy, Nicholas K.; Fernando, Daniel; Francis, Malcolm P.; Galván‐Magaña, Felipe; Hall, Martin; Heinrichs, Shawn; Marshall, Andrea; Mccauley, Douglas; Newton, Kelly M.; Notarbartolo‐Di‐Sciara, Giuseppe; et al.
Abstract: Manta and devil rays of the subfamily Mobulinae (mobulids) are rarely studied, large, pelagic elasmobranchs, with all eight of well‐evaluated species listed on the IUCN Red List as threatened or near threatened. Mobulids have life history characteristics (matrotrophic reproduction, extremely low fecundity, and delayed age of first reproduction) that make them exceptionally susceptible to overexploitation. Targeted and bycatch mortality from fisheries is a globally important and increasing threat, and targeted fisheries are incentivized by the high value of the global trade in mobulid gill plates. Fisheries bycatch of mobulids is substantial in tuna purse seine fisheries. Thirteen fisheries in 12 countries specifically targeting mobulids, and 30 fisheries in 23 countries with mobulid bycatch were identified. Aside from a few recently enacted national restrictions on capture, there is no comprehensive monitoring, assessment or control of mobulid fisheries or bycatch. Recent listing through the Convention on the International Trade in Endangered Species (CITES) may benefit mobulids of the genus Manta (manta rays), but none of the mobulids in the genus Mobula (devil rays) are protected. The relative economic costs of catch mitigation are minimal, particularly compared with a broad range of other, more complicated, marine conservation issues. Copyright © 2015 John Wiley & Sons, Ltd.